Clinical and MRI Evaluation of Orthodontic Mini-Screws for Disc Repositioning in Internal Derangement of TMJ: A Prospective Study - Rajkumar, K. (J Maxillofac Oral Surg, 2017)
PURPOSE: The purpose of this study was to assess the efficacy of orthodontic mini-screws as a modified suture anchor for disc repositioning in cases of internal derangement of the temporomandibular joint. PATIENTS AND METHODS: A prospective evaluation of ten patients was undertaken for a period of 6 months using this modified approach from Jan 2014 to Jun 2016. Symptomatic patients with clinical and MRI features suggestive of internal derangement of TMJ and willing to undergo surgical repositioning of articular disc to alleviate symptoms of temporomandibular dysfunction were taken up for the study. Post-operatively, functional outcomes were assessed in terms of reduction in pain, joint movement and absence of joint noise and clicking sounds. Post-operative MRI was used to assess the disc position and morphological changes in the disc and arthritic changes in the condyle. RESULTS: All patients underwent a surgical repositioning of the anteriorly displaced disc by the modified orthodontic suture anchor. Patients were post-surgically followed up at intervals of 1, 3 and 6 months. Immediate complications in terms of pain, restriction of functional motion and transient facial nerve palsy were noted. Late complications include temporal nerve palsy in one case. All patients experienced significant improvement with good functional outcomes and stable repositioning of disc was noticed at the end of 6 months. CONCLUSION: The modified disc repositioning using an orthodontic screw via a mini preauricular approach provided a good functional outcome in all patients as assessed over a period of 6 months. However, the long-term functional sequel of the procedure and changes in the articular disc needs to be assessed.